Enhancing Junior High School Students’ Mathematical Understanding through Augmented Reality Media Using Assemblr Edu: A Development Study - Mukaromah, Dwi Sofiatul; Kumala, Fitria Zana; Sardido, Joannah Mae C. (International Journal of Research in Mathematics Education, 2025)
Mathematical understanding ability is one of several basic mathematical abilities to be mastered and improved by students. Good mastery of this ability can support the development of advanced mathematical abilities. However, the students at SMPN 1 Paguyangan demonstrated low levels of mathematical understanding, which was partly due to monotonous lecture-based instruction and the rare use of interactive media to aid comprehension. This study aimed to develop Augmented Reality (AR)-based mathematics learning media using Assemblr Edu that were valid and effective in improving the mathematical understanding ability of ninth-grade students at SMPN 1 Paguyangan. The study employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results showed that the AR-based mathematics learning media developed using Assemblr Edu for the topic of "Three-Dimensional Shapes with Curved Surfaces" were declared valid and feasible, with scores of 80% from material experts, 91.6% from media experts, and 94.5% from mathematics teachers. Student responses were also positive, with average scores of 80.54% in the small group test and 78.48% in the field test. Furthermore, the pretest and posttest data were analyzed using an independent samples t-test, which produced a significance value of 0.000 (p < 0.05), leading to the rejection of H₀ and acceptance of H₁. The experimental group achieved an average N-Gain score of 0.771 (categorized as “High”), while the control group obtained a score of 0.357 (“Medium”), indicating that the developed learning media effectively improved students’ mathematical understanding.